Potential Role of SLC5A8 Expression in the Etiology of Subacute Ruminal Acidosis - Zhao, Chenxu; Bobe, Gerd; Wang, Yazhou; Zhang, Xinyue; Zhao, Zhibo; Zhang, Shiqi; Sun, Guoquan; Yuan, Xue; Li, Xinwei; Liu, Guowen (Frontiers in Veterinary Science, 2020)
Rumen fluid of cows with subacute ruminal acidosis (SARA) have high concentrations of short chain fatty acids (SCFA). However, the mechanism of SCFA accumulation is unknown. The solute-linked carrier 5a8 (SLC5A8) plays a key role in the transportation and absorption of SCFA in intestinal epithelium. The objective of the current study was to investigate (1) SLC5A8 gene and protein expression in various parts of the bovine gastrointestinal tract, (2) the effect of SCFA on SLC5A8 expression in rumen epithelial cells, and (3) SLC5A8 gene and protein expression in SARA and healthy cows. A total of 10 dairy cows, five in each group, SARA cows and control cows were 84 ± 26 days in milk and in their 2-4 parity. Three of adult cows and three calves (one-day-old, female, 45-50 kg, healthy, fasting) were chosen to collect total ten sections of digestive tract, from rumen to rectum, then bovine ruminal epithelial cells were isolated from three calves. Gene and protein expression of SLC5A8 was detected in all tested regions of gastrointestinal tract in calves and adult cows by western blot and quantitative real-time PCR, and were both highest in the rumen. Gene and protein expression of SLC5A8 was more than 50% lower in the rumen epithelium of SARA vs. Control cows and was partly restored after therapy of SARA cows. Compared with SCFA concentrations typical for control cows (60 mM acetate, 30 mM propionate and 20 mM butyrate), gene and protein expression of SLC5A8 in rumen epithelium was lower at elevated SCFA concentrations typical for SARA cows (90 mM acetate, 40 mM propionate and 30 mM butyrate); specifically for elevated concentrations of propionate or butyrate. In contrast, elevated concentrations of acetate increased gene and protein expression of SLC5A8 in rumen epithelium. In conclusion, the elevated concentrations of propionate and butyrate inhibit ruminal absorption of SCFA via downregulation of SLC5A8 in SARA cows, the expression of SLC5A8 plays important role in the etiology of SARA.